Third Order Optical Nonlinearity of Silver Nanoparticles Prepared by Chemical Reduction Method - Salloom, Hussein T (Al-Nahrain Journal of Science, 2017)
In this study, silver colloidal nanoparticles have been prepared by chemical reduction of silver nitrate by trisodium citrate as a reduction agent. The adding time of the reduction agent was held constant while the time of stirring was varied. The resulting silver nanoparticles were characterized by UV-VIS absorption spectroscopy. The non-linear refractive index and absorption coefficient of silver nanoparticles were investigated using a single beam z-scan technique. The excitation source was a continuous wave (CW) of 532 nm diode laser with a beam power of 40 mW. All investigated samples showed negative and large thermally-induced non-linear refractive indices. Other nonlinear optical parameters (i.e.β,χ_r^((3)),χ_i^((3))) were also calculated. Our measurements confirm that the non-linear parameters are caused by self-defocusing process making them potential candidates for nonlinear optical devices.